2022
DOI: 10.1085/jgp.202112980
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic spine morphology regulates calcium-dependent synaptic weight change

Abstract: Dendritic spines act as biochemical computational units and must adapt their responses according to their activation history. Calcium influx acts as the first signaling step during postsynaptic activation and is a determinant of synaptic weight change. Dendritic spines also come in a variety of sizes and shapes. To probe the relationship between calcium dynamics and spine morphology, we used a stochastic reaction-diffusion model of calcium dynamics in idealized and realistic geometries. We show that despite th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 111 publications
(220 reference statements)
2
39
0
Order By: Relevance
“…We found that there is a resetting of the bound‐AMPAR density (or percentage change) between the two spine shapes, despite the increase in spine volume (and volume‐to‐SA ratio) between the thin and mushroom spines. This trend matches the pattern found for synaptic weight updates based on Ca 2+ influx into dendritic spines of different sizes and geometries Bell et al, 2022. Therefore, we predict that thin spines are able to increase the density of bound‐AMPAR density more rapidly for increases in their volume; while in comparison, mushroom spines have a slower increase in density as volume increases.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We found that there is a resetting of the bound‐AMPAR density (or percentage change) between the two spine shapes, despite the increase in spine volume (and volume‐to‐SA ratio) between the thin and mushroom spines. This trend matches the pattern found for synaptic weight updates based on Ca 2+ influx into dendritic spines of different sizes and geometries Bell et al, 2022. Therefore, we predict that thin spines are able to increase the density of bound‐AMPAR density more rapidly for increases in their volume; while in comparison, mushroom spines have a slower increase in density as volume increases.…”
Section: Resultssupporting
confidence: 89%
“…We saw that at these timescales, despite the localization of receptors and channels for calcium, all cytosolic species other than cytosolic AMPARs showed homogeneous spatial dynamics. Therefore, due to this homogeneity and the previous investigation of these signalling species (Bell & Rangamani, 2021; Bell et al., 2019, 2022; Cugno et al., 2019; Ordyan et al., 2020), we will focus specifically on AMPAR spatiotemporal dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… In response to a glutamate release event coupled with a voltage stimulus [primarily, an EPSP and a backpropagating action potential (BPAP)], NMDA receptors (NMDARs) and voltage sensitive calcium channels (VSCCs) open on the spine membrane, resulting in an influx of Ca 2+ into the spine. Calcium influx into the spine is the first step in numerous different signalling pathways important for synaptic function and from a modelling perspective is one of the most studied events in spines (Bartol et al., 2015; Basnayake et al., 2019; Bell et al., 2019, 2022; Cugno et al., 2019; Leung et al., 2021; Li et al., 2012; Mahajan & Nadkarni, 2019; Ohadi & Rangamani, 2019; Ohadi et al., 2019). This voltage depolarization and subsequent calcium influx occurs over the millisecond time scale. Cytosolic Ca 2+ rapidly binds a variety of different species over the millisecond to second time scale, notably calmodulin (CaM) (Keller et al., 2008; Li et al., 2012; Stefan et al., 2008), which in turn triggers various kinases and phosphatases including calcium/calmodulin‐dependent protein kinase II (CaMKII) and protein phosphatase 1 (PP1) (Colbran, 2004; Mäki‐Marttunen et al., 2020; Pi & Lisman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This voltage depolarization and subsequent calcium influx occurs over the millisecond time scale. Cytosolic Ca 2+ rapidly binds a variety of different species over the millisecond to second time scale, notably calmodulin (CaM) (Keller et al., 2008; Li et al., 2012; Stefan et al., 2008), which in turn triggers various kinases and phosphatases including calcium/calmodulin‐dependent protein kinase II (CaMKII) and protein phosphatase 1 (PP1) (Colbran, 2004; Mäki‐Marttunen et al., 2020; Pi & Lisman, 2008). Free cytosolic Ca 2+ is also bound to various calcium buffers both in the cytoplasm and located on the membrane (Bell et al., 2019, 2022; Schmidt, 2012). CaM additionally binds to scaffolding proteins such as neurogranin (Ng), which impacts the available CaM for CaMKII activation (Ordyan et al., 2020; Prichard et al., 1999).…”
Section: Introductionmentioning
confidence: 99%